The effect of innovation orientation on firm performance: Evidence from micro and small manufacturing firms in selected towns of Awi Zone, Ethiopia - Samuel Godadaw Ayinaddis (Journal of Innovation and Entrepreneurship, 2023)
Innovation in micro and small enterprises is widely regarded as one of the most important sources of sustainable competitive advantage with an embedded purpose of performance improvement in an increasingly changing environment. This study aimed to examine the effect of innovation on the performance of micro and small manufacturing firms in selected towns of Awi Zone, Amhara, Ethiopia. The target population of the study was 643 micro and small manufacturing firms in Injibara, Dangila, and Tilili; a number provided by Awi zone enterprise development office data during 2021. Data were drawn from a sample of 247 manufacturing firms using cross-sectional primary data collected from wood and metal manufacturing firms in selected towns of Awi Zone. The study adopted descriptive and explanatory designs and used correlation and multiple linear regression analysis to estimate the effect of innovation on firm performance. The regression results revealed that product, process, marketing and organizational innovation were positively and significantly related to firm performance, while product innovation was found to have a strong positive effect on the dependent variable firm performance followed by process and organizational innovation, respectively. However, a weak statistical relationship was reported between marketing innovation and the performance of manufacturing firms than other variables. Hence, firms which have a strong orientation towards product, process, organizational and marketing innovation have better performance in manufacturing firms in the study area.
Keywords: 650; Innovation; Firm performance; MSEs; Awi Zone; Manufacturing firms